On Blue and Green Pigments from the St. George Cathedral of Veliky Novgorod - Alessandra R.G. Giumlia-Mair; Vladimir V. Sedov; Marina V. Vdovichenko; Maria Pia Riccardi (Advances in Archaeomaterials, 2022)
This paper presents the first analytical data obtained from the examination of fragments of stunning Russian–Byzantine frescoes recovered from an archaeological excavation at Veliky Novgorod, one of the oldest cities in Russia and a UNESCO World Heritage Site. The archaeologists of the Institute of Archaeology of the Russian Academy of Sciences have been working on architectural excavations at Novgorod for more than 20 years. In the last seven years, they have unearthed fragments of frescoes in the layers of the twelfth century AD during excavation under the floor of the Cathedral of St. George in the Yuriev Princely Monastery (built in 1119).As a first step of this complex research, we decided to concentrate on blue and green pigments. A selection of 30 samples and around 30 parts of wall paintings still in situ, subdivided by technique and color nuance, were first autoptically examined and, where possible, studied by optical microscopy. In this way typical details, such as the use of additives to the mortars, different ways of treating and mixing the colors, and pigment layers, were recognized. For the first screening, the analytical data were collected using a portable X-ray fluorescence device. They indicated the use of a variety of pigments and mixtures to obtain different nuances of color. The samples were then analyzed by scanning electron microscopy with energy dispersive spectrometry. All phases of the study were recorded and documented by photos and micrographs of the most significant details. The data are discussed in the text and help explain the working habits of the painters of the time.